Curious Deaths in the Russian Poetry of the 17th–18th Centuries - Кузнецова, Ольга (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The subject of the article is a poetic text from the manuscript in Tikhonravov’s collection, which is presented in the Russian State Library. It was created under the influence of medieval books, related to the theme of memento mori (Theatrum mortis humanae tripartitum). The poem describes three curious deaths, as an author qualifies them. Aegeus dies out of cowardice and the lack of wisdom when he saw the decrepit sails on his son’s ship, although Theseus came away from Crete with a victory. Aeschylus was killed because of his naivete when he was trying to avoid a prophecy saying that he would be killed by a falling of someone’s house, but an eagle dropped a tortoise on his head. Samson kills himself of excessive courage and the lack of wisdom. These stories, given in a poem as an exempla, are borrowed from the book Ifika Hieropolitics. When comparing these texts, one can see the technology of transcribing a prose text into a poetic text, which was used at the beginning of the 18th century. Lots of historical anecdotes about curious deaths have been known since antiquity. In the Middle Ages, they are grouped in literature on the theme of death. In Russia, this model was realised in the poetry of Simeon of Polotsk and flourished during the Baroque period. Such plots subsequently appeared in works of fiction and non-fiction, and not only in historical anecdotes, but also for characterising the absurdity of life and creating existential horror. Similarly to baroque texts, they still combine elements of the terrible and the curious.